Respons fisiologi dan profile metabolit sekunder Lima Kultivar Rambutan (Nephelium lappaceum L.) terhadap Penambahan Cahaya Buatan LED (Light Emitting Diode): Physiology and Secondary Metabolite Profiles Responses of Five Rambutan Varieties (Nephelium lappaceum L.) through Addition of Artificial Light LED (Light Emitting Diode) - Irsyad Maulana; Matra, Deden Derajat; Roedhy Poerwanto (Indonesian Society for Horticulture / Department of Agronomy and Horticulture, 2022)
Rambutan (Nephelium lappaceum L.) is a fruit that is suitable for growing in the tropics area. However, information on physiological responses and secondary metabolite profiles on artificial light treatment has not been reported. This study aims to study the response of rambutan plants to the application of artificial light from LED (Light Emitting Diode). The study was conducted in the screenhouse nursery using a two-factor nested plot design, namely LED as light source and cultivar. The LED light sources used red, blue, and white with application duration for 21 hours while the cultivars used Sikoneng, Parakan, Cilebak, Gravel, and Garuda cultivars. The results showed that rambutan plants that were given additional blue LEDs contained higher chlorophyll and leaf as glucose and fructose compared to another treatments. The results of the secondary metabolite profiles showed the largest Neophytadiene compound found in the Parakan cultivar under LED red treatment. Meanwhile, the compound that has the greatest abundance in white LEDs is 1-Propene, 3-[(4-nitrobutyl)thio]. Keywords: chlorophyll, photosynthesis, glucose, light spectrum, secondary metabolite